Expressing breastmilk while on break and in private: a qualitative study of Malaysian first-time mothers - Syed Hussien, Sh Fatimah Alzahrah; M. Shaw, Rhonda (Routledge, 2020)
Employment and breastfeeding among first-time mothers in Malaysia remain problematic, due, in part, to the lack of clear policies and policy implementation. This article, based on a phenomenological study utilising dyadic interviews with eight participants and twelve interviews, explores the experience of Malaysian first-time parents managing both breastfeeding and employment. The findings illustrate that although breastfeeding is considered a mother’s responsibility and is regarded as the preferred and superior form of infant feeding, there is often no designated time or space for expressing milk, causing many participants to use their lunch or tea breaks for this purpose. While study participants describe themselves as feeling supported by their partners, families, colleagues, and workplace superiors to breastfeed at work, they must nonetheless manage the perceived contradiction between the lactating body and the ‘male working body’. For these participants, this entails deftly negotiating the demands of being a good mother with a successful performance of the good worker role. Future research implications include a focus on identifying the roles and possible roles of fathers in infant feeding, and guidelines around monitoring breastfeeding breaks and spaces for mothers at work.